Heat pre-treatment can abolish anti-drug antibody interference in ligand binding pharmacokinetic assays - Svend Poulsen; Louise Jørgensen; Pia Søndergaard Galle (SpringerOpen, 2022)
Abstract Anti-drug antibodies (ADAs) can interfere with ligand binding assays (LBAs) by binding to epitopes recognized by the assay antibodies or by preventing assay antibody binding through steric hindrance. This can lead to underestimation of total drug concentration in pharmacokinetic (PK) samples which can confound decisions during drug development. We hypothesized that ADA interference in LBAs can be removed by sample heat pre-treatment. We heat pre-treated ADA-spiked samples by incubating them in a shallow water bath at 56-100 °C for 5-30 min prior to measuring the samples by a traditional electrochemiluminescence (ECL) assay. Heat pre-treatment at minimum 85 °C for 5 min completely removed the ADA interference. We then compared the analyte concentrations measured with and without heat pre-treatment of blood samples from toxicology studies performed for two different analytes in 60 cynomolgus monkeys and 29 minipigs, respectively. The overall difference in measured concentration of ADA-positive samples was significantly different from the overall difference in measured concentration of ADA-negative samples. For the cynomolgus monkey study samples, the ADA titer was determined, and the difference in measured concentration, when comparing heat pre-treatment to no heat pre-treatment, was significantly correlated to the ADA titer. Additionally, heat pre-treatment removed parallelism issues observed in a subset of study samples. Our data suggest that sample heat pre-treatment can abolish ADA interference in an LBA and could serve as a tool to assess the degree of ADA interference and the total drug concentration in a PK sample. Of note, before utilizing this strategy on a new analyte, it is necessary to assess whether heat pre-treatment negatively affects the detection of the analyte by the assay antibodies.